Cerium-doped ferronickel-based composite catalytic material as well as preparation method and application thereof

By using cerium-doped nickel-iron-based composite catalytic material in alkaline electrolytic hydrogen production technology, the problem of insufficient anode activity and stability is solved, and an efficient and stable hydrogen production process of electrolytic water is achieved, reducing energy consumption and cost .

CN119392290AActive Publication Date: 2025-02-07BEIJING UNIV OF CHEM TECH +1

Patent Information

Application Number
CN202411820419.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-02-07
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

In the existing alkaline electrolytic hydrogen production technology, the activity and stability of the anode are insufficient, resulting in high energy consumption and high cost, and the formation process is complex and the stability is insufficient.

Method used

A cerium-doped nickel-iron-based composite catalytic material, which includes a foam nickel-based substrate and a cerium-doped nickel-iron-based electrode layer coated thereon, forms a porous structure through the complexation of citric acid and cerium ions in the electroplating solution. The electrode layer improves activity and stability.

Benefits of technology

In the process of alkaline electrolysis hydrogen production, the activity and stability of the catalytic material are improved, the precipitation amount of metal elements and the risk of falling off of the electrode layer are reduced, and the electrolytic efficiency and life are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392290A_ABST
    Figure CN119392290A_ABST
Patent Text Reader

Abstract

The invention relates to the field of hydrogen production by alkaline electrolysis of water, and discloses a cerium-doped ferronickel-based composite catalytic material and a preparation method and application thereof, the cerium-doped ferronickel-based composite catalytic material comprises a foamed nickel substrate and a cerium-doped ferronickel-based electrode layer coating at least part of the foamed nickel substrate; the mass ratio of a cerium element to a nickel element to an iron element in the cerium-doped nickel-iron-based electrode layer is 1: (60-75): (20-40); and the average pore diameter of the cerium-doped nickel-iron-based electrode layer is 1-3 microns. The attenuation rate of an electrode layer of the cerium-doped ferronickel-based composite catalytic material is smaller than or equal to 0.05 mV / h under 1000 h, the precipitation amount of a nickel element is smaller than or equal to 2 micrograms / L under 1000 h, the precipitation amount of an iron element is smaller than or equal to 100 micrograms / L, and the cerium-doped ferronickel-based composite catalytic material has excellent oxygen evolution activity and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of hydrogen production by alkaline water electrolysis, and in particular to a cerium-doped nickel-iron-based composite catalytic material and a preparation method and application thereof. Background Art

[0002] At present, the mainstream way to produce hydrogen is through fossil fuel reforming, which will produce a lot of carbon emissions. Therefore, it is particularly urgent to develop sustainable hydrogen production technology to meet the growing energy demand. Water electrolysis technology is an effective way to store renewable energy by converting electrical energy into chemical energy. Coupling it with solar and wind energy to produce hydrogen can effectively solve the instability of renewable energy generation. Common water electrolysis technologies include alkaline water electrolysis (ALK) and proton exchange membrane water electrolysis (PEMWE), as well as emerging anion exchange membrane water electrolysis (AEMWE). Among them, ALK has the longest development time and has been commercialized, but its electrolysis efficiency is low and its ohmic impedance is large, resulting in more energy consumption. PEMWE has a zero-gap structure, low ohmic impedance, and can achieve a higher current density, but it requires the use of precious metal catalysts with low element abundance and high prices, which limits its large-scale application. AEMWE combines the advantages of ALK and PEMWE, which can achieve high current density and use non-precious metal catalysts, reducing the energy consumption and cost of water electrolysis to produce hydrogen. However, the activity and stability of AEMWE anode need to be further improved.

[0003] CN101748426A discloses a method for preparing a foam electrode for water electrolysis, wherein foam nickel is selected as a substrate of an electrode material, the surface of the foam nickel is degreased to make the surface clean, the foam nickel is soaked in a dilute acid solution, the foam nickel is surface activated, the activated foam nickel is rinsed with pure water, and the foam nickel is quickly immersed in an electrodeposition tank as a cathode for electrodeposition to prepare an active surface, the foam electrode on the active surface is thoroughly cleaned, and then dried and heat-treated, and the foam material after the heat treatment is cut to make an electrode material. This prior art can reduce the overpotential of hydrogen precipitation in the electrolysis process to a certain extent, reduce energy consumption, and improve production efficiency. However, it has the defects of complex generation process and insufficient stability. Summary of the invention

[0004] The purpose of the present invention is to provide a composite catalytic material for alkaline water electrolysis having both excellent activity and stability.

[0005] In order to achieve the above-mentioned object, the first aspect of the present invention provides a cerium-doped nickel-iron-based composite catalytic material, the cerium-doped nickel-iron-based composite catalytic material comprising: a foamed nickel substrate, and a cerium-doped nickel-iron-based electrode layer coated on at least a portion of the foamed nickel substrate;

[0006] The mass ratio of cerium element, nickel element and iron element in the cerium-doped nickel-iron based electrode layer is 1:60-75:20-40;

[0007] The average pore size of the cerium-doped nickel-iron-based electrode layer is 1-3 μm; the attenuation rate of the cerium-doped nickel-iron-based electrode layer at 1000 h is ≤0.05 mV / h, the precipitation amount of nickel element is ≤2 μg / L, and the precipitation amount of iron element is ≤100 μg / L at 1000 h.

[0008] The second aspect of the present invention provides a method for preparing the cerium-doped nickel-iron-based composite catalytic material described in the first aspect, the method comprising:

[0009] (1) in the presence of water, nickel salt, ferrous salt, cerium nitrate, citric acid, a conductive agent and a pH buffer are contacted and mixed to obtain an electroplating solution; in the electroplating solution, the concentration of the citric acid is 0.02-0.035 mol / L, and the concentration of the cerium ion is 5-15 mmol / L;

[0010] (2) Immersing the nickel foam in an electroplating solution for electrodeposition treatment to obtain the cerium-doped nickel-iron-based composite catalytic material.

[0011] The third aspect of the present invention provides an application of the cerium-doped nickel-iron-based composite catalytic material described in the first aspect in hydrogen production by electrolysis of water.

[0012] The technical solution provided by the present invention has at least the following advantages:

[0013] The cerium-doped nickel-iron-based composite catalytic material provided by the present invention introduces cerium elements to improve the surface morphology of the cerium-doped nickel-iron-based electrode layer, and the surface has a porous structure, so that it has abundant active sites, thereby improving the activity. The cerium-doped nickel-iron-based electrode layer provided by the present invention also has excellent stability, reduces the precipitation of metal elements during the oxygen evolution process, and the cerium-doped nickel-iron-based electrode layer is firmly combined with the foam nickel substrate and is not easy to fall off.

[0014] In the preparation method of the cerium-doped nickel-iron-based composite catalytic material provided by the present invention, the composite action of citric acid and cerium nitrate makes the surface of the electrode layer have a porous structure, so that it has abundant active sites, thereby improving the activity, and the electrode layer is firmly bonded to the foamed nickel substrate, which can effectively prevent the electrode layer from falling off under high current density. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a scanning electron microscope image of the composite catalytic material synthesized using electroplating solutions with different citric acid concentrations;

[0016] Figure 2 Is to use different Ce 3+ SEM images of composite catalytic materials synthesized by electroplating solution with a concentration of 1.

[0017] Figure 3 It is a scanning electron microscope image of the composite catalytic material synthesized by using electroplating solution with different electrodeposition time;

[0018] Figure 4 This is a scanning electron microscope image of the composite catalytic material without cerium doping;

[0019] Figure 5 It is the X-ray diffraction analysis diagram of the composite catalytic material;

[0020] Figure 6 It is the linear sweep voltammetric curve of the composite catalytic material synthesized by using electroplating solution with different citric acid concentrations;

[0021] Figure 7 Is to use different Ce 3+ Linear sweep voltammetric curves of composite catalytic materials synthesized by electroplating solutions with different concentrations;

[0022] Figure 8 It is the linear sweep voltammetric curve of the composite catalytic material synthesized by using the electroplating solution with different electrodeposition time;

[0023] Fig. 9 is a linear sweep voltammetric graph of a nickel foam metal substrate and a composite catalyst material that has not been electrodeposited;

[0024] Fig.10 It is a chronopotentiometric curve diagram of a composite catalytic material without cerium doping and a cerium doped nickel-iron based composite catalytic material;

[0025] Fig.11 This is a scanning electron microscope image of the composite catalytic material after stability testing;

[0026] Fig.12 It is the pore size analysis diagram of the composite catalytic material;

[0027] Fig.13 It is the X-ray photoelectron spectrum of composite catalytic materials;

[0028] Fig.14 is a linear sweep voltammetric curve diagram of the composite catalytic material of Example 1 and Comparative Example 5;

[0029] Fig.15 It is the linear sweep voltammetry curve diagram of the composite catalytic material of Example 1 and Comparative Example 6. DETAILED DESCRIPTION

[0030] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0031] The average pore size described in the present invention refers to the average pore diameter.

[0032] As mentioned above, the first aspect of the present invention provides a cerium-doped nickel-iron-based composite catalytic material, the cerium-doped nickel-iron-based composite catalytic material comprising: a foamed nickel substrate, and a cerium-doped nickel-iron-based electrode layer coated on at least a portion of the foamed nickel substrate;

[0033] The mass ratio of cerium element, nickel element and iron element in the cerium-doped nickel-iron based electrode layer is 1:60-75:20-40;

[0034] The average pore size of the cerium-doped nickel-iron-based electrode layer is 1-3 μm; the attenuation rate of the cerium-doped nickel-iron-based electrode layer at 1000 h is ≤0.05 mV / h, the precipitation amount of nickel element is ≤2 μg / L, and the precipitation amount of iron element is ≤100 μg / L at 1000 h.

[0035] The cerium-doped nickel-iron-based composite catalytic material provided by the present invention has excellent activity and stability, and is not prone to dissolution of metal components and shedding of the electrode catalytic layer under alkaline oxygen evolution conditions.

[0036] Preferably, in the cerium-doped nickel-iron-based composite catalytic material provided by the present invention, the foamed nickel substrate is coated with the cerium-doped nickel-iron-based electrode layer.

[0037] Preferably, the thickness of the cerium-doped nickel-iron-based electrode layer is 5-20 μm.

[0038] Preferably, based on the total mass of the cerium-doped nickel-iron-based electrode layer, the sum of the contents of cerium, nickel and iron is 70-90 wt %.

[0039] Preferably, the cerium-doped nickel-iron-based electrode layer is -2 The lower overpotential is ≤300 mV, preferably ≤290 mV, more preferably ≤285 mV, and particularly preferably ≤280 mV.

[0040] Preferably, the surface density of the nickel foam is 300-400 g / m 2 , the porosity is 75-98%.

[0041] As mentioned above, the second aspect of the present invention provides a method for preparing the cerium-doped nickel-iron-based composite catalytic material described in the first aspect, the method comprising:

[0042] (1) in the presence of water, nickel salt, ferrous salt, cerium nitrate, citric acid, a conductive agent and a pH buffer are contacted and mixed to obtain an electroplating solution; in the electroplating solution, the concentration of the citric acid is 0.02-0.035 mol / L, and the concentration of the cerium ion is 5-15 mmol / L;

[0043] (2) Immersing the nickel foam in an electroplating solution for electrodeposition treatment to obtain the cerium-doped nickel-iron-based composite catalytic material.

[0044] The present invention specifically selects cerium nitrate as the source of cerium element. The inventors have found that this technical feature can make the cerium-doped nickel-iron-based composite catalytic material have better activity and stability, reduce the precipitation rate of metal elements, and improve oxygen evolution activity. In addition, the composite effect of citric acid and cerium elements makes the surface of the electrode layer have a porous structure, so that it has abundant active sites, thereby improving the activity, and the electrode layer is firmly combined with the foam nickel substrate, which can effectively prevent the electrode layer from falling off at high current density.

[0045] The present invention adopts ferrous salt in the electroplating solution, which has the advantages of lower overpotential and better stability compared with trivalent iron ions, thereby obtaining a cerium-doped nickel-iron-based composite catalytic material with higher activity and stability.

[0046] Preferably, in the electroplating solution, the molar concentration ratio of cerium ions, nickel ions and ferrous ions is 1:6-20:6-20, more preferably 1:10-20:10-20.

[0047] Preferably, in the electroplating solution, the concentration of nickel ions is 0.05-0.2 mol / L, preferably 0.08-0.12 mol / L; the concentration of ferrous ions is 0.05-0.2 mol / L, preferably 0.08-0.12 mol / L; the concentration of cerium ions is 5-10 mmol / L.

[0048] Preferably, in the electroplating solution, the concentration of the citric acid is 0.02-0.025 mol / L;

[0049] Preferably, in the electroplating solution, the concentration of the conductive agent is 0.5-1.5 mol / L;

[0050] Preferably, in the electroplating solution, the concentration of the pH buffer is 0.2-0.5 mol / L.

[0051] Preferably, the nickel salt is nickel sulfate and / or nickel chloride.

[0052] Preferably, the ferrous salt is ferrous sulfate and / or ammonium ferrous sulfate.

[0053] Preferably, the conductive agent is selected from at least one of ammonium chloride, ammonium sulfate, potassium sulfate and sodium chloride; preferably ammonium chloride and / or ammonium sulfate.

[0054] Preferably, the pH buffer is selected from at least one of boric acid, phosphoric acid and oxalic acid; preferably boric acid.

[0055] The nickel salt, the ferrous salt, the cerium nitrate and the citric acid in the present invention may be in a hydrated form or a non-hydrated form, and there is no particular limitation on the amount of bound water. Water and compounds known in the art may be used. For example, nickel sulfate hexahydrate, ferrous sulfate heptahydrate, cerium nitrate hexahydrate and citric acid monohydrate may be used. The present invention will not be described in detail again, and those skilled in the art should not interpret this as a limitation of the present invention.

[0056] Preferably, the electrodeposition treatment time is 10-20 minutes.

[0057] According to a particularly preferred embodiment of the present invention, the operation of the electrodeposition treatment includes:

[0058] The nickel foam was used as the working electrode and the graphite sheet was used as the counter electrode. A two-electrode system was used at 25-75 mA·cm -2 The cerium-doped nickel-iron-based composite catalytic material is obtained by constant current deposition at a current density of , and the deposition time is 10-20 minutes.

[0059] Preferably, the nickel foam is in the form of a sheet, relative to 4 cm 2 The volume of the electroplating solution is 0.1-0.2 L. It should be noted that the area of ​​the nickel foam here refers to the single-side area.

[0060] The nickel foam of the present invention can be in regular flakes or irregular flakes, and those skilled in the art can cut it into any shape according to actual needs. The present invention will not be described in detail again, and those skilled in the art should not be construed as limiting the present invention.

[0061] According to a preferred specific implementation manner, the method further comprises: firstly subjecting the nickel foam to a degreasing treatment and a surface activation treatment in sequence, and then subjecting the pretreated nickel foam to the electrodeposition treatment.

[0062] In some embodiments, the degreasing treatment comprises: immersing the nickel foam in an organic solvent and ultrasonically cleaning it for 20-40 minutes.

[0063] Preferably, the organic solvent is selected from at least one of acetone, petroleum ether and ethyl acetate.

[0064] In some embodiments, the surface activation treatment comprises: immersing the degreased nickel foam in an acid solution for ultrasonic treatment for 20-40 minutes to obtain the pretreated nickel foam; the hydrogen ion concentration in the acid solution is 2.5-3.5 mol / L.

[0065] Preferably, the acid solution is selected from at least one of a hydrochloric acid solution and a sulfuric acid solution.

[0066] According to a particularly preferred embodiment, before the nickel foam is subjected to degreasing treatment, the nickel foam is first subjected to a rolling treatment so that the surface density is 300-400 g / m 2 .

[0067] The method described in the present invention may also include conventional post-processing means in the art, such as cleaning and drying, which can be selected by those skilled in the art according to the technical means known in the art. The present invention exemplifies a preferred specific implementation method in the following text, which should not be construed as a limitation of the present invention by those skilled in the art.

[0068] As mentioned above, the third aspect of the present invention provides an application of the cerium-doped nickel-iron-based composite catalytic material described in the first aspect in hydrogen production by electrolysis of water.

[0069] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the raw materials are all commercially available.

[0070] Nickel foam: purchased from Kunshan Guangjiayuan New Materials Co., Ltd.

[0071] In the following examples, unless otherwise specified, the following method is used to pretreat nickel foam:

[0072] Commercial nickel foam was rolled to 270 μm (surface density 300-400 g / m 2 ), and then cut into a size of 2cm×2cm. The cut nickel foam is ultrasonically cleaned in acetone for 30 minutes to remove surface oil stains, and the cleaned nickel foam is taken out and dried naturally. The dried nickel foam is ultrasonically cleaned in 3mol / L hydrochloric acid for 30 minutes to remove the surface oxide layer, and the cleaned nickel foam is rinsed with deionized water 3 times, and then washed with anhydrous ethanol 3 times to remove the residual hydrochloric acid on the surface, and dried naturally to obtain the pretreated nickel foam (NF).

[0073] Example 1

[0074] (1) dissolving nickel sulfate hexahydrate, ferrous sulfate heptahydrate, cerium nitrate hexahydrate, ammonium chloride, boric acid and citric acid monohydrate in deionized water, and uniformly mixing to obtain a green transparent solution, namely, an electroplating solution;

[0075] The nickel ion concentration in the electroplating solution is 0.1 mol / L, the ferrous ion concentration is 0.1 mol / L, the cerium ion concentration is 5 mmol / L, the monohydrate citric acid concentration is 0.025 mol / L, the ammonium chloride concentration is 1 mol / L, and the boric acid concentration is 0.4 mol / L.

[0076] (2) The pretreated nickel foam was used as the working electrode and the graphite sheet was used as the counter electrode. They were immersed in 0.1 L of electroplating solution to form a two-electrode system at -50 mA cm -2 The deposited nickel foam was rinsed with deionized water 3 times and ethanol 3 times, and dried in an oven at 50°C for 2h to prepare a cerium-doped nickel-iron-based composite catalytic material (named NiFeCe 0.05 -2.5-10mins / NF), the average pore size of the cerium-doped nickel-iron-based composite catalytic material is 1-3μm; the sum of the contents of cerium, nickel and iron in the electrode layer is 85wt%, and the mass ratio of cerium, nickel and iron is 1:69:29.

[0077] Example 2

[0078] The process was similar to that of Example 1, except that the concentration of citric acid monohydrate was adjusted to 0.02 mol / L, and the rest remained unchanged to prepare a cerium-doped nickel-iron-based composite catalyst material (named NiFeCe 0.05 -2-10mins / NF).

[0079] Example 3

[0080] The process was similar to that of Example 1, except that the concentration of citric acid monohydrate was adjusted to 0.03 mol / L, and the rest remained unchanged to prepare a cerium-doped nickel-iron-based composite catalyst material (named NiFeCe 0.05 -3-10mins / NF).

[0081] Example 4

[0082] The same process as in Example 1 was used, except that the concentration of citric acid monohydrate was adjusted to 0.035 mol / L, and the rest remained unchanged to prepare a cerium-doped nickel-iron-based composite catalyst material (named NiFeCe 0.05 -3.5-10mins / NF).

[0083] Example 5

[0084] The process was similar to that of Example 1, except that the amount of cerium nitrate hexahydrate was adjusted so that the concentration of cerium ions in the electroplating solution was 10 mmol / L, and the concentrations of other metal ions remained unchanged; a cerium-doped nickel-iron-based composite catalyst material (named NiFeCe 0.1 -2.5-10mins / NF).

[0085] Example 6

[0086] The process was similar to that in Example 1, except that the electrodeposition time was adjusted to 15 mins; the rest remained unchanged to prepare a cerium-doped nickel-iron-based composite catalyst material (named NiFeCe 0.05 -2.5-15mins / NF).

[0087] Example 7

[0088] The process was similar to that of Example 1, except that the electrodeposition time was adjusted to 20 mins; the rest remained unchanged to prepare a cerium-doped nickel-iron-based composite catalyst material (named NiFeCe 0.05 -2.5-20mins / NF).

[0089] Comparative Example 1

[0090] The process was similar to that of Example 1, except that the concentration of citric acid monohydrate was adjusted to 0.01 mol / L, and the rest remained unchanged to prepare a cerium-doped nickel-iron-based composite catalyst material (named NiFeCe 0.05 -1-10mins / NF).

[0091] Comparative Example 2

[0092] The process was similar to that of Example 1, except that the concentration of citric acid monohydrate was adjusted to 0.015 mol / L, and the rest remained unchanged to prepare a cerium-doped nickel-iron-based composite catalyst material (named NiFeCe 0.05 -1.5-10mins / NF).

[0093] Comparative Example 3

[0094] The process was similar to that of Example 1, except that the amount of cerium nitrate hexahydrate was adjusted so that the concentration of cerium ions in the electroplating solution was 20 mmol / L, and the concentrations of other metal ions remained unchanged; a cerium-doped nickel-iron-based composite catalyst material (named NiFeCe 0.2 -2.5-10mins / NF).

[0095] Comparative Example 4

[0096] A similar process to Example 1 was adopted, except that cerium nitrate hexahydrate was not added to the electroplating solution in step (1), and the rest remained unchanged to prepare a nickel-iron based composite catalyst material (named NiFe / NF).

[0097] Comparative Example 5

[0098] The process is similar to that of Example 1, except that the ferrous sulfate heptahydrate in step (1) is replaced by ferric nitrate nonahydrate (chemical formula Fe(NO3)3·9H2O), and the concentration of iron ions in the electroplating solution is kept unchanged; a cerium-doped nickel-iron-based composite catalytic material (named NiFeCe 0.05 -Fe(NO3)3·9H2O / NF).

[0099] Comparative Example 6

[0100] The process is similar to that of Example 1, except that citric acid monohydrate is not used in step (1), that is, the electroplating solution does not contain citric acid; the rest remain unchanged; and a cerium-doped nickel-iron-based composite catalyst material (NiFeCe 0.05 - Citric Acid Free / NF).

[0101] Test Example 1

[0102] The composite catalytic materials synthesized by using electroplating solutions with different citric acid concentrations (Examples 1 to 4, Comparative Examples 1 to 2) were analyzed by scanning electron microscopy. The surface morphology thereof is as follows: Figure 1 As shown in the figure, it can be seen that the surface electrode catalyst layer of the cerium-doped nickel-iron-based composite catalyst material provided by the present invention has a more excellent pore distribution and size.

[0103] For different Ce 3+ The composite catalytic materials (Example 1, Example 5 and Comparative Example 3) synthesized by electroplating solution with a concentration of Figure 2 As shown in the figure, it can be seen that the surface electrode catalyst layer of the cerium-doped nickel-iron-based composite catalyst material provided by the present invention is porous, with moderate pore size distribution and porosity. The surface electrode catalyst layer of the cerium-doped nickel-iron-based composite catalyst material obtained without the scheme of the present invention is transformed from a porous structure into nanoparticles, and gradually agglomerates.

[0104] The composite catalytic materials (Example 1, Example 6 and Example 7) synthesized by using different electrodeposition times were analyzed by scanning electron microscope. The surface morphology thereof is as follows: Figure 3 As shown in the figure, it can be seen that the cerium-doped nickel-iron-based composite catalytic material provided by the present invention has a porous structure with uniform pore distribution and moderate pore size.

[0105] The composite catalytic material without cerium doping (Comparative Example 4) was analyzed by scanning electron microscope, and its surface morphology is as follows: Figure 4 As shown in the figure, compared with the sample doped with cerium, the NiFe / NF catalyst layer has no porous structure on its surface, and its surface active sites will be reduced, which is not conducive to the improvement of oxygen evolution activity.

[0106] The pore size analysis of the composite catalytic material obtained in Example 1 was performed, and the results were as follows: Fig.12 As shown in the figure, it can be seen that the pore size of the electrode layer on the surface of the composite catalytic material is mostly around 1 μm.

[0107] Test Example 2

[0108] For Example 1 (NiFeCe 0.05 -2.5-10mins) and comparative example 4 (NiFe / NF) were subjected to X-ray diffraction (XRD) analysis of the electrode layer of the composite catalytic material. The results are as follows Figure 5 As shown, the XRD data indicate that the electrode layer is mainly composed of alloy phase materials of Ni and Fe, wherein the diffraction peaks of 44.5°, 51.8° and 76.4° belong to the (111), (200) and (220) crystal planes of Ni, respectively, while the diffraction peaks of 44.7°, 65.0° and 82.3° belong to the (110), (200) and (211) crystal planes of Fe, respectively.

[0109] Fig.13 is the X-ray photoelectron spectrum of the composite catalytic material (Example 1); NiFeCe 0.05 The 2p orbital analysis of Ni in the -2.5-10mins / NF sample shows that the characteristic peak at the binding energy of 852.5eV is attributed to Ni 0 , and the characteristic peak at 855.8eV belongs to Ni 2+ , its binding energy shifts to a lower direction relative to NiFe / NF, proving that the valence state of Ni is lower than that of NiFe / NF. XPS analysis of Fe 2p orbital shows that the peak at 707 eV belongs to Fe 0 , and the characteristic peak at 711.1 eV belongs to Fe 2+ , its binding energy shifts to a lower direction relative to NiFe / NF, proving that the valence state of Ni is lower than that of NiFe / NF. The 3d orbital of Ce shows that the characteristic peaks at 879.5eV and 885.4eV belong to Ce. 3+ , while the characteristic peaks at 882.2eV and 887.4eV belong to Ce 4+ .

[0110] Test Example 3

[0111] Activity and stability test of composite catalytic materials: Prepare 1 mol / L potassium hydroxide solution as the test electrolyte, use the synthesized composite catalytic material sample as the working electrode, the graphite electrode as the counter electrode, and the saturated calomel electrode as the reference electrode, and fully immerse these three electrodes in the prepared electrolyte to form a three-electrode system. Use linear sweep voltammetry to determine the catalytic activity of the oxygen evolution reaction, and use chronopotentiometry to determine the catalytic stability of the oxygen evolution reaction.

[0112] Figure 6 The linear sweep voltammetric curves are of composite catalytic materials (Examples 1 to 4, Comparative Examples 1 to 2) synthesized using electroplating solutions with different citric acid concentrations. It can be seen from the figure that the cerium-doped nickel-iron-based composite catalytic material provided by the present invention has high oxygen evolution activity.

[0113] Figure 7 To adopt different Ce 3+ The linear sweep voltammetric curves of the composite catalytic materials (Example 1, Example 5, Comparative Example 3 and Comparative Example 4) synthesized from the electroplating solution of 100% and 200% concentrations show that the introduction of cerium can effectively increase the active sites on the surface of the catalytic layer, thereby improving the activity. 0.05 -2.5-10mins / NF) has the highest oxygen evolution activity, reaching 100mA·cm -2 The overpotential required for the current density is 1.505 V (vs. reversible hydrogen electrode RHE).

[0114] Figure 8 The linear sweep voltammetric curves of the composite catalytic materials (Example 1, Example 6, Example 7) synthesized with different electrodeposition times are shown in the figure. It can be seen from the figure that the cerium-doped nickel-iron-based composite catalytic material provided by the present invention has excellent oxygen evolution activity.

[0115] Fig. 9 The linear sweep voltammetric curves of the nickel foam metal substrate (NF) and the composite catalyst material (Example 1) without electrodeposition are shown in Figure 1. It can be found that compared with other different embodiments, the activity of NF is the worst at 100 mA·cm -2 The overpotential is as high as 383mV at a current density of 2.58kV.

[0116] Fig.10 The chronopotentiometry curves are for the composite catalytic material without cerium doping (Comparative Example 4) and the cerium doped nickel-iron based composite catalytic material (Example 1); the electrodeposition time is 10 mins, at 200 mA·cm -2 The chronopotentiometry curves under the NiFeCe 0.05-2.5-10mins / NF has only increased its overpotential by 40mV after 1000h chronopotentiometry, while NiFe / NF has increased its overpotential by 11mV after 130h chronopotentiometry. Its decay rate is NiFeCe 0.05 -2.5-10mins / NF twice.

[0117] Fig.11 is a scanning electron microscope image of the composite catalytic material of Example 1 and Comparative Example 4 after stability test, wherein NiFeCe 0.05 -2.5-10mins / NF at 200mA·cm -2 After running for 1000h, the electrode layer did not fall off, and the pore structure of the electrode layer surface was well preserved. This shows that the composite catalytic material provided by the present invention has high mechanical stability, the electrode catalytic layer structure is not easily destroyed and is firmly combined with the nickel foam metal substrate, showing good stability, while the nanoparticles on the surface of the NiFe / NF sample catalytic layer are seriously agglomerated, and the catalytic layer becomes thinner, and the outline of the nickel foam metal substrate is clearly visible.

[0118] Fig.14 The linear sweep voltammetry curves of Example 1 and Comparative Example 5 are shown in Table 1. It can be found that the plating solution contains Fe 3+ , the oxygen evolution reaction (OER) activity of the sample will deteriorate at 100 mA cm -2 The overpotential is as high as 318mV at a current density of .

[0119] Fig.15 The linear sweep voltammetry curves of Example 1 and Comparative Example 6 are shown in Figure 1. It can be found that when the plating solution does not contain citric acid, the OER activity of the sample will deteriorate. -2 The overpotential is as high as 312mV at a current density of 2.58kV.

[0120] Test Example 4

[0121] The thickness of the electrode layer of the composite catalytic material prepared in the above-mentioned embodiments and comparative examples is shown in Table 1.

[0122] The metal element precipitation content of the electrolyte after the composite catalytic material chronopotentiometric test is tested. The test method is: high-frequency inductively coupled plasma is used as an excitation light source to excite the gaseous atoms or ions in the sample material. The outer electrons after being excited will emit characteristic radiation energy due to electron transition in the process of returning to the ground state. The corresponding energy information is captured and then compared with the energy information of the standard sample at different contents to obtain the content of the measured element. The present invention exemplarily provides data on the metal element precipitation content of the electrolyte after the composite catalytic material chronopotentiometric test of Example 1 and Comparative Example 4, as shown in Table 2.

[0123] The overpotential and decay rate of the composite catalytic materials prepared in the aforementioned embodiments and comparative examples were tested.

[0124] The overpotential test method is: in the actual electrochemical performance test of oxygen evolution half-reaction, the measured potential will have a certain difference with the thermodynamic theoretical electrode potential, and this difference is the overpotential. Under the same anode current density, the smaller the overpotential, the higher the OER catalytic activity of the sample. The oxygen evolution activity is tested by linear sweep voltammetry to obtain 100mAcm -2 The potential at the current density is 1.23 V minus the theoretical OER electrode potential, which is 1.23 V, to obtain 100 mA cm -2 The results are shown in Table 3.

[0125] The decay rate was tested by chronopotentiometry at 200 mA cm -2 During charging, the decay rate can be obtained by dividing the value of the overpotential increase by the time.

[0126] The composite catalytic material prepared by the technical solution provided by the present invention has excellent activity and stability. The decay rate of the composite catalytic material of Example 1 is 0.04 mV / h, while the decay rates of the composite catalytic materials of Comparative Examples 3 and 4 are 0.57 mV / h and 0.085 mV / h, respectively, and the stability is significantly poor.

[0127] Table 1

[0128] Nomenclature of composite catalytic materials Thickness of electrode layer (μm) Example 1 <![CDATA[NiFeCe 0.05 -2.5-10mins / NF]]> 10 Example 2 <![CDATA[NiFeCe 0.05 -2-10mins / NF]]> 10 Example 3 <![CDATA[NiFeCe 0.05 -3-10mins / NF]]> 10 Example 4 <![CDATA[NiFeCe 0.05 -3.5-10mins / NF]]> 10 Example 5 <![CDATA[NiFeCe 0.1 -2.5-10mins / NF]]> 10 Example 6 <![CDATA[NiFeCe 0.05 -2.5-15mins / NF]]> 12 Example 7 <![CDATA[NiFeCe 0.05 -2.5-20mins / NF]]> 14 Comparative Example 1 <![CDATA[NiFeCe 0.05 -1-10mins / NF]]> 10 Comparative Example 2 <![CDATA[NiFeCe 0.05 -1.5-10mins / NF]]> 10 Comparative Example 3 <![CDATA[NiFeCe 0.2 -2.5-10mins / NF]]> 10 Comparative Example 4 NiFe / NF 10

[0129] Table 2

[0130]

[0131] Table 3

[0132] Nomenclature of composite catalytic materials <![CDATA[100mA·cm -2 Lower overpotential (mV)]]> Example 1 <![CDATA[NiFeCe 0.05 -2.5-10mins / NF]]> 275 Example 3 <![CDATA[NiFeCe 0.05 -3-10mins / NF]]> 281 Example 4 <![CDATA[NiFeCe 0.05 -3.5-10mins / NF]]> 295 Example 5 <![CDATA[NiFeCe 0.1 -2.5-10mins / NF]]> 279 Example 6 <![CDATA[NiFeCe 0.05 -2.5-15mins / NF]]> 292 Example 7 <![CDATA[NiFeCe 0.05 -2.5-20mins / NF]]> 286 Comparative Example 3 <![CDATA[NiFeCe 0.2 -2.5-10mins / NF]]> 294 Comparative Example 4 NiFe / NF 298 Comparative Example 5 <h2 style=";text-align:left;direction:ltr"><![CDATA[NiFeCe <h2 style=";text-align:left;direction:ltr"> 0.05 <h2 style=";text-align:left;direction:ltr"> -Fe(NO3)3·9H2O / NF]]><h2 style=";text-align:left;direction:ltr"> 318 Comparative Example 6 <![CDATA[NiFeCe 0.05 -Citric Acid Free / NF]]> 312 Nickel foam after pretreatment NF 383

[0133] It can be seen from the above results that the cerium-doped nickel-iron-based electrode layer provided by the present invention also has excellent activity and stability, reduces the precipitation of metal elements during oxygen evolution, and the cerium-doped nickel-iron-based electrode layer is firmly bonded to the foamed nickel substrate and is not easy to fall off.

[0134] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A cerium-doped nickel-iron-based composite catalytic material, characterized in that: The cerium-doped nickel-iron-based composite catalytic material comprises: a foamed nickel substrate, and a cerium-doped nickel-iron-based electrode layer coated on at least a portion of the foamed nickel substrate; The mass ratio of cerium element, nickel element and iron element in the cerium-doped nickel-iron based electrode layer is 1:60-75:20-40; The average pore size of the cerium-doped nickel-iron-based electrode layer is 1-3 μm; the attenuation rate of the cerium-doped nickel-iron-based electrode layer at 1000 h is ≤0.05 mV / h, the precipitation amount of nickel element is ≤2 μg / L, and the precipitation amount of iron element is ≤100 μg / L at 1000 h.

2. The cerium-doped nickel-iron-based composite catalytic material according to claim 1, characterized in that: The thickness of the cerium-doped nickel-iron-based electrode layer is 5-20 μm; And / or, based on the total mass of the cerium-doped nickel-iron-based electrode layer, the sum of the contents of cerium, nickel and iron is 70-90 wt %.

3. The cerium-doped nickel-iron-based composite catalytic material according to claim 1 or 2, characterized in that: The cerium-doped nickel-iron-based electrode layer is at 100 mA·cm -2 Lower overpotential ≤300mV.

4. A method for preparing the cerium-doped nickel-iron-based composite catalytic material according to any one of claims 1 to 3, characterized in that: The method includes: (1) in the presence of water, nickel salt, ferrous salt, cerium nitrate, citric acid, a conductive agent and a pH buffer are contacted and mixed to obtain an electroplating solution; in the electroplating solution, the concentration of the citric acid is 0.02-0.035 mol / L, and the concentration of the cerium ion is 5-15 mmol / L; (2) Immersing the nickel foam in an electroplating solution for electrodeposition treatment to obtain the cerium-doped nickel-iron-based composite catalytic material.

5. The method according to claim 4, characterized in that In the electroplating solution, the concentration of nickel ions is 0.05-0.2 mol / L, and the concentration of ferrous ions is 0.05-0.2 mol / L; and / or, in the electroplating solution, the molar concentration ratio of cerium ions, nickel ions and ferrous ions is 1:6-20:6-20; and / or, in the electroplating solution, the concentration of the citric acid is 0.02-0.025 mol / L; and / or, in the electroplating solution, the concentration of the conductive agent is 0.5-1.5 mol / L; And / or, in the electroplating solution, the concentration of the pH buffer is 0.2-0.5 mol / L.

6. The method according to claim 4, characterized in that The nickel salt is nickel sulfate and / or nickel chloride; And / or, the ferrous salt is ferrous sulfate and / or ammonium ferrous sulfate.

7. The method according to claim 4, characterized in that The conductive agent is selected from at least one of ammonium chloride, ammonium sulfate, potassium sulfate and sodium chloride; And / or, the pH buffer is selected from at least one of boric acid, phosphoric acid and oxalic acid.

8. The method according to claim 4, characterized in that The electrodeposition treatment time is 10-20 minutes; and / or, relative to 4 cm 2 The volume of the nickel foam is 0.1-0.2L.

9. The method according to any one of claims 4 to 8, characterized in that: The method further comprises: firstly subjecting the nickel foam to degreasing treatment and surface activation treatment in sequence, and then subjecting the pretreated nickel foam to the electrodeposition treatment.

10. Use of the cerium-doped nickel-iron-based composite catalytic material according to any one of claims 1 to 3 in hydrogen production by water electrolysis.

Citation Information

Patent Citations

  • Preparation method of foam electrode for water electrolysis

    CN101748426A

  • Method for assisted in-situ modification of three-dimensional nickel-iron hydrotalcite electro-catalytic oxygen evolution electrode by using nickel foam matrix surface cerium ions

    CN110354862A

  • Preparation method of denitration catalyst

    CN112958064A

  • Nickel-iron-cerium catalytic material, preparation method thereof and application of nickel-iron-cerium catalytic material in electrolyzed water

    CN117248219A

  • Method for preparing alkaline electrolysis water electrode through electro-deposition

    CN118345425A

Cited By

  • Cerium-doped amorphous nickel-phosphorus alloy hydrogen evolution electrode and preparation method and application thereof

    CN122169139A